Improving Students' Questioning Skills Level through Inquiry Training Learning Using Digital Learning Tools - Abdul Aziz Rahman (Jurnal Report of Biological Education, 2021)
Background: One of the important student abilities is questioning. The observations of SMPN 2 Kadudampit students showed low student questioning ability. Thus, this research aims to find out the usefulness of digital learning tools for blended learning with an inquiry training model to improving students' questioning skills. Method:  pre-experimental design. The subject of the study was a grade 8A student at SMPN 2 Kadudampit. To collect data on this study, questioning levels observation sheets, observation sheets of student activities in learning, and interview sheets of students. The data is analyzed quantifiably using T-Test and described.  Result: Learning inquiry training assisted by digital learning tools can be carried out with the highest percentage of student activities at the highest learning by 70%. The average ability to ask students at synthetic levels is 36% of the total student questions. Conclusion: From the results of the study can be concluded that through learning inquiry training assisted digital tools can improve the ability to ask students at a higher level than before.